The impact of COVID‐19 severity on adult survivors: Is there a relationship between vascular reactivity and cardiorespiratory fitness? - Guilherme Dionir Back; Murilo Rezende Oliveira; Guilherme Peixoto Tinoco Arêas; Patricia Faria Camargo; Cássia daLuz Goulart; Claudio Ricardo deOliveira; José Carlos Bonjorno Junior; Flávia Rossi Caruso Bonjourno; Ross Arena; Audrey Borghi‐Silva (Physiological Reports)
Abstract The impact of COVID‐19 on cardiorespiratory fitness (CRF) is negative, increasing the likelihood of exertional symptoms such as fatigue and shortness of breath, and adversely affecting vascular function, impairing cardiovascular health. This study investigated endothelial function and its relationship with CRF in patients who have recovered COVID‐19. Patients were evaluated 1 month after infection, including clinical assessment, pulmonary function, endothelial function (measured by flow‐mediated dilation), and cardiopulmonary exercise testing. COVID‐19 survivors exhibited reduced exercise capacity, with poor values of peak V̇O2peak and FMD (%) according to disease severity. However, endothelial function was worse in COVID‐19 patients, regardless of severity, compared to the control group. Significant associations were observed between poorer FMD (%) and peak V̇O2, workload, circulatory power, and V̇O2peak/WR. Endothelial function was significantly associated with CRF in COVID‐19 patients according to disease severity. Strategies to improve CRF and reduce the negative impacts of endothelial function damage should be further investigated.